Beyond students: how teacher psychology shapes educational inequality. Issue 8 (August 2021) - Turetsky, Kate M.; Sinclair, Stacey; Starck, Jordan G.; Shelton, J. Nicole
Abstract : Although researchers investigating psychological contributors to educational inequality have traditionally focused on students, a growing literature highlights the importance of teachers' psychology in shaping disparities in students' educational achievement and attainment. In this review, we discuss recent advances linking teachers' attitudes, perceptions, and beliefs to inequality in students' outcomes. First, we identify specific aspects of teacher psychology that contribute to educational disparities, including teachers' biases, perceptions and expectations of students, beliefs about the nature of ability, and beliefs about group differences. Second, we synthesize mechanisms underlying the effects of teacher psychology on educational inequality, including teachers' disparate assessment of students' work and abilities, interpersonal interaction with students, and psychological impact on students. Implications for future research and interventions are discussed. Highlights: Emerging research traces the effects of teachers on inequality in students' educational achievement and attainment, moving beyond a historical focus on students. This research has identified specific aspects of teacher psychology that contribute to disparities in students' outcomes as well as the mechanisms underlying these effects. These advances have important theoretical and practical implications for the field's understanding of the sources of educational inequality and efforts to promote equity. In particular, this literature suggests that teachers may be a high-impact target for psychological interventions to reduce educational inequality.